Imaging of Thoracic and Lumbar Intervertebral Disc Herniation Cases with MRI: A Retrospective Study - Pamuk, Kamuran (Progress in Nutrition, 2021)
Study Objectives: The objective of this study was to make a comparison between the results of the neurological examination performed due to suspected IVDD (Intervertebral Disk Degeneration) and thoracolumbar spinal cord trauma and the findings of MRI (Magnetic Resonance Imaging) of 26 dogs and four cats that were referred to the center with such complaints as paraplegia, paralysis, incoordination, and urine incontinence/retention. Methods: A neurological examination involving quadriceps (patellar) reflex, flexor pedal reflex, panniculus reflex, and anal reflex was performed on a total of 30 patients (26 dogs and 4 cats), their radiographs were taken, and an MRI procedure was applied under anesthesia. Results: MRIs of the cases that were referred to Pamuk Veterinary Therapy Center between March 2018 and May 2021 were taken in transverse, coronal (dorsal), and sagittal planes as T1-weighted (T1W), T2-weighted (T2W). It was figured out that, in 65.4 percent of the dogs the discs between L1 and L7 were exposed to a greater impact compared to other regions, while the rate was 75 percent for cats. All cases were diagnosed with disc degeneration; accordingly, eight of the dogs had Type I, nine Type II, and nine Type III, while two cats had Type I, one Type II, and one Type III. For dogs, a significant correlation was found between body weight, PR, and IVDS; however, no significant correlation was observed between PR, IVDS (Intervertebral Disc Space), and species, breed, gender, or age. Conclusion: Based on the results of this study it can be argued that the findings obtained through panniculus reflex examination performed on lesional thoracic and lumbar disc regions can be used in combination with MRI, providing a clinically acceptable consistency rate.